Myanmar : Rice Price Reduction and Poverty Reduction - World Bank Group (Washington, DC, 2015)
Myanmar is a low-income agrarian country with a high poverty rate. The livelihood of many poor people depends on the performance of agriculture, especially the rice sector. Rice accounts for 70 percent of Myanmar s total cultivated area and 30 percent of the value of its agricultural production. Increasing returns to rice production will be the key to increasing farm wages and incomes in the short to medium run. Higher rice production will also help maintain low food prices, improve food security, and reduce poverty, as an average household spends 61 percent of total household income on food, and rice is a major component of the food basket. Price fluctuations are a common feature of well-functioning agricultural markets. Price fluctuation should be expected in such markets, since output varies from period to period due to factors such as weather, pests and disease, and because demand and supply are inelastic in the short run. Moreover, some amount of seasonal and spatial price movements should be tolerated, since these usefully signal scarcity in the market and facilitate a supply response, foster arbitrage between surplus and deficit regions, as well as guide post-harvest handling, storage and trade decisions. However, in the case of Myanmar s rice market, several factors serve to exacerbate price fluctuation and make them more pronounced and unpredictable (volatile) and lead to serious negative impacts for consumers and farmers. Rice price volatility is of concern to the Myanmar government given the high importance of rice for farm incomes and consumer expenditures, and thereby for food security and poverty reduction. On the production side, prices volatility inhibits farmers supply response and is a disincentive for greater use of purchased inputs and increased investments. Volatility can also discourage rice-producing farmers to diversify their cropping patterns to high-value crops if they cannot buy cereals for consumption at more predictable prices. On the consumption side, rice price spikes can cause increased food insecurity for those not wealthy enough to maintain consumption levels at the higher prices. For people spending 50 percent of their income on rice, a 20 percent temporary increase in rice prices would lead to an approximate 10 percent decline in effective income. This is a large shock, often equivalent to households spending on health and education.